A Closer Look at the Diffuse and Localised Necking of A Metallic Thin Sheet: Evolution of the Two Bands Pattern. (June 2016) - Bao, C.; Francois, M.; Le Joncour, L.
Abstract: Plastic strain localisation in a sheet specimen was monitored by electronic speckle pattern interferometry during uniaxial tensile tests. The experiments were carried on in the diffuse and localised necking stages until fracture. A kinematic model, which is independent of material characteristics, was used to describe the whole strain rate field with two crossing localisation bands inclined with respect to the tensile direction. Then, the physical features of localisation, such as the width of the two bands, their inclination angles and their maximum strain rates are identified by least‐square from the displacements fields and their evolutions are followed from the onset of diffuse necking up to the failure. In particular, the effect of the average strain rate is considered and bandwidth evolution is analysed in detail. It was found that: The band structure appears early, as soon as diffuse necking starts; The separation, in terms of strain rate or bandwidth, of the two bands corresponds to the transition between diffuse and localised necking. The localised necking stage can be divided into two sub‐stages: in the first one, the two bands continue to evolve but at different rates, and in the second one, one of the bands stabilises. The transition between the two sub‐stages is influenced by the crossbeam velocity; The inclination of the band leading to fracture remains quite stable, while the other rotates towards a situation perpendicular to the tensile direction; The band width decreases exponentially versus the maximum local strain. The two bands follow the same evolution path, but one of them progressively lags behind the other until it stops deforming. Although the average strain rate was only varied by a factor two, it was found that, when the strain rate increases, the two bands stay together longer and thus that the onset of localised necking is delayed.